2017
DOI: 10.18632/oncotarget.22654
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic changes in cerebrospinal fluid from primary central nervous system lymphoma patients are associated with protein ectodomain shedding

Abstract: Primary central nervous system lymphomas (PCNSLs) are mature B-cell lymphomas confined to the central nervous system (CNS). Blood-brain barrier (BBB) dysfunction drastically alters the cerebrospinal fluid (CSF) proteome in PCNSL patients. To reveal the interaction of PCNSL tumors with CNS structures and the vasculature, we conducted a whole-proteome analysis of CSF from PCNSL patients (n = 17 at initial diagnosis) and tumor-free controls (n = 10) using label-free quantitative mass spectrometry. We identified 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 53 publications
6
13
0
Order By: Relevance
“…Removal of 375 plasma proteins which likely appear as a result of plasma leakage due to BBB disruption allowed us to avoid false-positive candidate biomarkers [17]. Detailed data analysis and immunohistochemistry confirmed the results from a previous study which showed that more than half of the proteins with significant abundance changes in the CSF of PCNSL patients originated mainly from the surrounding CNS tissue instead of the lymphoma tissue [13]. Here, we speculate that the lymphoma tissue interacts and communicates with its environment (CNS tissue) that causes the release of proteinaceous factors by different secretory pathways (ectodomain shedding).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Removal of 375 plasma proteins which likely appear as a result of plasma leakage due to BBB disruption allowed us to avoid false-positive candidate biomarkers [17]. Detailed data analysis and immunohistochemistry confirmed the results from a previous study which showed that more than half of the proteins with significant abundance changes in the CSF of PCNSL patients originated mainly from the surrounding CNS tissue instead of the lymphoma tissue [13]. Here, we speculate that the lymphoma tissue interacts and communicates with its environment (CNS tissue) that causes the release of proteinaceous factors by different secretory pathways (ectodomain shedding).…”
Section: Discussionsupporting
confidence: 76%
“…This holds also true for the comparison of PCNSL with SCNSL (51%), PCNSL with gliomas (56%), PCNSL with "other tumors" (55%) and PCNSL with MS (52%) ( Table 2). We also identified a high number of secreted and membrane proteins among the differentially abundant proteins which is in concordance with our former observations [13]. As the second criterion for the selection of candidate biomarkers, we considered the diagnostic accuracy determined by the ROC analysis of the individual peptide intensities determined by label-free mass spectrometry (Table 4, Figure S1A-E).…”
Section: Discovery Study: Identification Of Candidate Biomarkers By Qsupporting
confidence: 83%
See 2 more Smart Citations
“…In clinical samples, several types of shed ectodomains have been identified in the biological fluids of cancer patients. A study performed on the cerebrospinal fluid proteome of patients with primary central nervous system lymphoma showed increased presence of 36 shed membrane proteins, which could be further examined and validated as possible biomarkers . In general, many of the disease‐related shed proteins are various types of adhesion molecules such as CAM proteins, cadherins, and CD44.…”
Section: Discovery Of Protease Substratesmentioning
confidence: 99%